The Ethiopian emergency medical team: its formation, progress, response experience and opportunities - Oyugi, Boniface; Tadelle, Nahom; Gebreyesus, Alegnta; Lazaro, Martinez-Monterrey; Mbasha, Jerry-Jonas; Relan, Pryanka; Balde, Thierno; Salio, Flavio; Abtea, Melkamu; Zeynu, Neima; Okeibunor, Joseph (Frontiers in Public Health, 2025)
BackgroundEthiopia faces climate shocks, conflict, food insecurity, and limited livelihoods, creating urgent humanitarian needs and a critical demand for emergency medical response. A well-coordinated national emergency medical team (N-EMT) is essential to address these crises effectively.ObjectiveThis study documents the progress of the country's emergency response mechanisms and N-EMT development, highlights lessons learned for other countries implementing emergency medical teams (EMTs) and concludes with recommendations for improvement.MethodsThis study employed a holistic single-case study design, integrating mixed methods approaches to explore the introduction and establishment of N-EMT in the Federal Republic of Ethiopia. It examined the national disaster response context, highlighting key challenges, enabling factors, and emergent opportunities. Data were collected through key informant interviews (KIIs) and an in-depth review of relevant policy and operational documents. The study utilizes the guiding framework for implementing N-EMTs in addition to thematically documenting lessons learnt.ResultsLaunched in August 2018, the Ethiopian Disaster Medical Assistance Team (DMAT) initiative aimed to enhance Ethiopia's response to rising emergencies in peripheral regions by establishing a structured framework with trained professionals. This led to the creation of N-EMTs and a strategic implementation roadmap, supported by a core team executing a comprehensive joint work plan. Collaborating with partners and utilizing existing government systems ensured resource management and access to essential supplies. Strong backing from the Ministry of Health (MoH) and high-level government offices was vital for integration and sustainability, emphasizing political will's role in advancing health frameworks. The N-EMT expanded to address mass gatherings, conflicts, and malnutrition, enhancing capabilities and participating in regional health diplomacy. Collaborations with United Kingdom Medical Emergency Team (UK-MED) and Polish Center for International Aid (Polskie Centrum Pomocy Miedzynarodowej) (PCPM) refined verification, human resource (HR) management, and logistics, supported by innovative funding. Ethiopia's N-EMT implementation score reached 69 out of 96, indicating substantial progress toward full operationalization. Of the total implementation activities, 27 were fully completed, 15 were partially achieved or ongoing, and 6 had yet to commence. Key lessons learned emphasized the importance of streamlined resource management, the establishment of advance teams, robust preparedness measures, coordinated response mechanisms, and the provision of psychological support following deployments.ConclusionEthiopia has made strong and measurable progress in developing its N-EMT, establishing a foundational framework, mobilizing trained personnel, and expanding its scope to address a variety of emergencies. However, to reach full WHO classification, specific gaps remain—particularly in institutionalizing coordination structures, formalizing deployment protocols, and strengthening logistics and human resource systems. This experience highlights the importance of embedding N-EMTs within the national health and emergency response systems, backed by sustained political commitment, strategic partnerships, and dedicated investment in capacity building and preparedness infrastructure.